Technology Acceptance Model in Tiktok Shop Adoption - Pratama, Muhammad Rizqi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Virtual shopping has grown rapidly in the first two decades of the 21st century, driven by advances in information and communications technology and mobile devices. TikTok, a video sharing application from China, has introduced a shopping feature called TikTok Shop, which has attracted the attention of researchers studying its adoption. This research aims to understand the factors that influence the adoption and use of TikTok Shop in Indonesia. This research uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. Data was collected through an electronic questionnaire distributed to TikTok users in Indonesia. Data analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The research results show that performance expectancy, social influence, facilitating conditions, price value, hedonic motivation, and habit have a positive influence on attitude and behavioral intention. Apart from that, attitude also has a positive influence on behavioral intention, which in turn influences consumer trust behavior relationship between behavioral intention and use behavior, strengthening this relationship. This research provides insight for technology developers and marketers about the key factors that drive e-commerce adoption through social media platforms such as TikTok Shop increasing the use of TikTok Shop in Indonesia.